2018
DOI: 10.5194/acp-18-15669-2018
|View full text |Cite
|
Sign up to set email alerts
|

Ice-nucleating ability of aerosol particles and possible sources at three coastal marine sites

Abstract: Abstract. Despite the importance of ice-nucleating particles (INPs) for climate and precipitation, our understanding of these particles is far from complete. Here, we investigated INPs at three coastal marine sites in Canada, two at mid-latitude (Amphitrite Point and Labrador Sea) and one in the Arctic (Lancaster Sound). For Amphitrite Point, 23 sets of samples were analyzed, and for Labrador Sea and Lancaster Sound, one set of samples was analyzed for each location. At all three sites, the ice-nucleating abil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 96 publications
6
31
0
Order By: Relevance
“…Although Al, Si, Ca, and Fe were found at low concentrations ( Fig. 8a), Tables 2 and S2 suggest that mineral dust particles are an important source of INPs in Sisal at temperatures ranging from −20 to −30 • C. This is in close agreement with the results obtained by Si et al (2019) in the Canadian High Arctic. From the correlation of the [INP] and the aerosol chemical composition at −15 • C, Mg was the only element showing a correlation that is statistically significant at the 95 % confidence interval (p < 0.05).…”
Section: Identification Of the Potential Inp Sourcessupporting
confidence: 89%
“…Although Al, Si, Ca, and Fe were found at low concentrations ( Fig. 8a), Tables 2 and S2 suggest that mineral dust particles are an important source of INPs in Sisal at temperatures ranging from −20 to −30 • C. This is in close agreement with the results obtained by Si et al (2019) in the Canadian High Arctic. From the correlation of the [INP] and the aerosol chemical composition at −15 • C, Mg was the only element showing a correlation that is statistically significant at the 95 % confidence interval (p < 0.05).…”
Section: Identification Of the Potential Inp Sourcessupporting
confidence: 89%
“…8). Multiple photochemical processes occur in the sea ice-snow-atmosphere system of the Arctic, acting upon the variation between bromide and sodium (Simpson et al, 2007;Jacobi et al, 2012). On solid surfaces (aerosols, snow, sea ice) bromide can be transformed into volatile bromine compounds that are released to the atmosphere and subsequently deposited.…”
Section: Bromide In the Snowpackmentioning
confidence: 99%
“…Therefore, bromide can be already depleted in the sea salt aerosols generated over sea ice, which would cause a wet and dry deposition flux lower than estimated based on the standard seawater ratio, or it can be diminished in the surface snow after deposition (Jacobi et al, 2012), explaining the average bromide-to-sodium ratios below the seawater ratio in both snow pits. Nevertheless, since the released bromide is subsequently deposited, a snowpack with layers enriched in bromide is also possible depending on the dominating influence of the release vs. the additional deposition of bromide (Simpson et al, 2007). This can also explain the contrasting results found on top of the Holtedahlfonna glacier, located approximately 40 km to the northeast of Ny-Ålesund, in April 2012.…”
Section: Bromide In the Snowpackmentioning
confidence: 99%
“…CC BY 4.0 License. with results from Si et al (2018) and Irish et al (2019a), both done in the Arctic, where it was also concluded that SSA only contributed little to the INP population.…”
Section: Discussionmentioning
confidence: 68%